Pendampingan Pengembangan Karakter Individu Sebagai Penggiat Pencegahan Pemberantasan Penyalahgunaan dan Peredaran Gelap Narkotika (P4GN) Pada Kalangan Masyarakat di Kabupaten Bogor - Nur Laela Ermaya, Husnah; Kalifatullah Ermaya, Sir (LPPM Universitas Koperasi Indonesia, 2024)
The circulation of illegal drugs continues to increase every year. The volume of drug circulation is directly proportional to the number of users. Bogor Regency has the second highest number of drug cases in West Java (Jabar). A total of 170 drug cases have been handled by the police in 2022. The Bogor Police Narcotics Unit throughout the year has been trying to reduce the number of drug users and dealers by carrying out preventive efforts in collaboration with other stakeholders. This activity aims to provide education to all participants who attend about the impacts of using illegal drugs and how to overcome them. Apart from that, it also forms the individual character of every P4GN activist in Bogor Regency.